URGENSI BAHASA ARAB SEBAGAI BAHASA INTERNASIONAL DALAM PENDIDIKAN ISLAM - Ahmadi, Maswan; Awaluddin, A. Fajar (Atta'dib Jurnal Pendidikan Agama Islam, 2024)
There is a perception that Arabic is a language exclusively for followers of Islam. It is undeniable that one reason people study Arabic is to understand Islamic teachings. However, when we examine the current development of the Arabic language, it has become an international language of communication that plays a crucial role in inter-country cooperation to advance Islamic education. This is due to the fact that many countries, including world universities, have adopted Arabic as a subject of study. Mastering Arabic as a language of communication will open broader opportunities for collaboration to enhance Islamic education. This study is a descriptive library research that illustrates the urgency of Arabic as an international language in Islamic education. The study reveals a new direction in the use of Arabic, where it was previously considered a religious language, but now has become an international language, offering numerous benefits in terms of educational, economic, cultural, and knowledge development.